(untitled) (International journal of artificial intelligence, 2025)
This thesis explores the pedagogical possibilities of preparing students for creative activity based on a creative approach. The creative approach creates the necessary conditions for the development of students’ ability to think freely, generate new ideas, and solve problems using innovative methods. The thesis analyzes the theoretical foundations of the creative approach, methods of its implementation in the educational process, as well as ways to develop problem-based learning and divergent thinking. In addition, the role of the teacher in supporting creative activity, creating a creative environment, and evaluating students’ creative performance is discussed. The thesis reveals important aspects of fostering creativity in the pedagogical process and demonstrates the potential of modern educational technologies to enhance students’ creative abilities.